PENGARUH KUALITAS AUDIT, KEPEMILIKAN PUBLIK, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK: Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018 - Gusti Ayu Novy Sumardeni; Gde Herry Sugiarto Asana (Universitas Triatma Mulya, 2021)
Tax aggressiveness is a specific activity, including transactions that aim to reduce corporate tax obligations. The purpose of this study is to obtain empirical evidence about the effect of audit quality, public ownership, and corporate social responsibility on tax aggressiveness measured using cash effective tax rates. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. Determination of the sample using non-probability sampling method with purposive sampling technique and obtained 34 manufacturing companies. The analysis technique used is multiple linear analysis. Based on the results of the analysis concluded that audit quality has a negative effect on tax aggressiveness, public ownership has a negative effect on tax aggressiveness, and corporate social responsibility has a negative effect on tax aggressiveness.